Bromopropylate Imidazoliumyl Substituted Silicon Phthalocyanine for Mitochondria-Targeting, Two-Photon Imaging Guided in Vitro Photodynamic Therapy - Chen, Kuizhi; Hou, Jialin; Huang, Bingcheng; Xiao, Shuanghuang; Li, Xia; Sun, Hong; Peng, Yiru (Frontiers in Pharmacology, 2022)
Maximization of phototoxic damage on tumor is essential for effective anticancer photodynamic therapy (PDT). Highly cancer-cell-organelle-specific delivery of efficient photosensitizers (PSs) in vitro and in vivo is in great demand. In this paper, a novel water-soluble mitochondria targeted cationic bromopropylate imidazoliumyl axially substituted silicon (IV) phthalocyanine (Br-ID-SiPc) is developed to improve PDT efficiency by enhancing the subcellular localization of photosensitizers. Benefiting from the targeting capability of bromopropylate imidazoliumyl, Br-ID-SiPc can selectively accumulate in mitochondria after cellular uptake, this process could be tracked by two-photon imaging. Br-ID-SiPc effectively damaged the circular plasmid DNA of mitochondria and induced HO-8910 cells apoptosis. Our results indicate that Br-ID-SiPc is a potential photosensitizer which can be used as a mitochondria-targeting and two-photon fluorescent imaging molecule for PDT of cancers.